2020
DOI: 10.1038/s41598-020-62423-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the activity of HIV-1 protease through antibody binding and mutations probed by molecular dynamics simulations

Abstract: HIV-1 protease is an essential enzyme in the life cycle of the HIV-1 virus. The conformational dynamics of the flap region of the protease is critical for the ligand binding mechanism, as well as for the catalytic activity. The monoclonal antibody F11.2.32 raised against HIV-1 protease inhibits its activity on binding. We have studied the conformational dynamics of protease in its free, inhibitor ritonavir and antibody bound forms using molecular dynamics simulations. We find that upon Ab binding to the epitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…Meanwhile, these methods can facilitate the ease of finding antiviral drugs for SARS-CoV-2[36]. In the case of HIV-1 protease, these were applied to find the loss of flexibility in the mutants which can inhibit protease activity[37].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, these methods can facilitate the ease of finding antiviral drugs for SARS-CoV-2[36]. In the case of HIV-1 protease, these were applied to find the loss of flexibility in the mutants which can inhibit protease activity[37].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the exibility of the ap-tip region in chain-B (residues Gly51-Phe53) of MUT-Pr-D was remarkably increased compared with that of WT-Pr-D. It has been shown that increasing the ap-tip exibility facilitate opening of the active-site gate, which consequently facilitate releasing the inhibitor from active-site 10,12,63 . The highly affected residues as a result of mutations in both WT-Pr and MUT-Pr complexes were illustrated by superposed 20 trajectory structures, with 10 ns intervals (Fig.…”
Section: Comparison Of the Exibility Of The Ap-tipsmentioning
confidence: 99%
“…The ap-tips are glycine-rich domains with hairpin structure, which control the access of substrate/inhibitor to the activesite 7 . It has been shown both computationally and experimentally that the HIV-1 PR has three possible that are classi ed based on the distance between two ap-tips [8][9][10][11][12] . In the ligand-bound form, the aptips take a downward conformation relative to the active-site (closed state), while the free form permanently takes a semi-open conformation 13,14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lopinavir is an inhibitor of Human Immunodeficiency Virus 1 (HIV-1) protease (19). The metabolism of lopinavir can be delayed by ritonavir to enhance the anti-HIV-1 effect of lopinavir; therefore, these two drugs are often used in combination (20).…”
Section: Lopinavir/ritonavirmentioning
confidence: 99%